2016
DOI: 10.1097/hjh.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, treatment, and control in 115 rural and urban communities involving 47 000 people from China

Abstract: In China, hypertension is common, and while recent studies suggest some improvements, more than half of affected individuals were unaware that they had hypertension. Rates of control remain low. National programs effective in preventing and controlling hypertension in China are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
95
5
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 23 publications
12
95
5
4
Order By: Relevance
“…These are in keeping with findings from studies of other ethnic groups, which compared measures between rural and urban areas591821. Over half the nomads in the sample had hypertension, which may be explained by the long-term physical labour in animal husbandry and their dietary habits (more than 90% of nomads drink milk tea, and vegetables and fruits are not a staple).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These are in keeping with findings from studies of other ethnic groups, which compared measures between rural and urban areas591821. Over half the nomads in the sample had hypertension, which may be explained by the long-term physical labour in animal husbandry and their dietary habits (more than 90% of nomads drink milk tea, and vegetables and fruits are not a staple).…”
Section: Discussionsupporting
confidence: 84%
“…The results of this study are similar to a cross-sectional survey conducted in Fukang pastoral area, Xinjiang, in 200817. However, compared with the PURE study (participants aged 35–70 years) conducted in China5, individuals’ awareness was higher (61.0% vs 41.6%) and the proportions on treatment or with controlled blood pressure were lower (28.8% vs 34.4% and 2.9% vs 8.2%, respectively), suggesting that healthcare in remote areas is still sub-optimal. Higher salt intake was strongly associated with higher blood pressures and prevalence of hypertension, and negatively associated with awareness, treatment, and control.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…China also participated in the Prospective Urban Rural Epidemiological (PURE) study,53 which enrolled individuals aged 35–70 years from 17 countries to examine primary risk factors for obesity, hypertension, dysglycemia dyslipidemia, and cardiovascular diseases. In China, 115 (45 urban and 70 rural) communities from 12 provinces participated, and 46,285 persons were recruited from 2005 to 2009 54. Participants were followed for incident cardiovascular disease and death for 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of hypertension is increasing and showing a trend of becoming an accelerating epidemic [3,4]. Previous studies have reported that the prevalence of hypertension was higher in urban than in rural communities [5,6,7], but some recent studies showed that the prevalence of hypertension in rural areas exceeded that in the urban districts in China [4]. Northern China is a high hypertension incidence area, and the northern rural areas also face a grim hypertension status.…”
Section: Introductionmentioning
confidence: 99%